Long‐term survival of dogs treated for gallbladder mucocele by cholecystectomy, medical management, or both. (6th September 2019) - Parkanzky, Max; Grimes, Janet; Schmiedt, Chad; Secrest, Scott; Bugbee, Andrew
Abstract: Background: Gallbladder mucoceles (GBM) typically are treated by cholecystectomy. Medical management rarely has been reported and medical and surgical management have not been compared. Hypothesis/Objectives: To compare survival of dogs treated for GBM by medical management or cholecystectomy or both. Animals: Eighty‐nine client‐owned dogs diagnosed with GBM that received cholecystectomy or medical treatment or both from 2011 to 2017. Methods: Potential cases were identified by searching the medical records database. Data collected included signalment, clinicopathologic results, treatments, and ultrasonographic images and reports. Dogs were grouped according to the treatment received (medical management, surgical treatment, or both) that was chosen at the discretion of the attending veterinarian. Survival analysis was performed and prognostic variables identified and compared between treatment groups. Results: Of dogs surviving at least 14 days after diagnosis, median survival times were 1802 (95% confidence interval [CI], 855‐not reached) days, 1340 (95% CI, 444‐1340) days, and 203 (95% CI, 18‐525) days, for the surgical, medical, and medical then surgical treatment groups, respectively, and differed significantly ( P < .0001). Gallbladder mucocele type ( P = .05), serum alkaline phosphatase activity ( P = .0001), and serum creatinine ( P = .002) and phosphorus ( P = .04) concentrations were associated with decreased survival across groups. Suspicion of biliary rupture on abdominal ultrasound (AUS) examination was correlated with increased survival in the surgical group ( P = .02). Conclusions and clinical importance: Cholecystectomy for the treatment of GBM results in the best long‐term survival in dogs surviving the immediate postoperative period (14 days) compared to medical management. Although medical management is associated with shorter survival compared to surgical treatment, it is a reasonable alternative when surgery cannot be pursued.